Did the Silk Road(s) Extend from Dunhuang, Mount Wutai, and Chang’an to Kyoto, Japan? A Reassessment Based on Material Culture from the Temple Gate Tendai Tradition of Miidera - Keyworth, George (Dynamics in the history of religions, 2022)
Did the Silk Road(s) actually extend to early or medieval Japan? In this paper I take the two Tendai (天台) pilgrims to China who are central to the Jimon (寺門) tradition of Mii Temple (Jap. Miidera 三井寺), Enchin (814-891, 円珍, Chishō daishi 智証大師) and Jōjin (1011-1081, 成尋), as bookends to answer the question: did the Silk Road(s) extend to Japan through the Jimon Tendai tradition during the 9th-11th centuries? In the first section of the paper I outline how the materials listed in travel diaries and catalogues (Jap. shōrai mokuroku 請来目録) of the books, statues, and ritual objects brought back by Enchin confirm that the Buddhism he imported from the continent can be connected to cosmopolitan ritual practices that flourished along the eastern Silk Road(s) even after the Huichang era (840-845, 會昌) persecution of foreign faiths. One of the earliest statues of an indigenous kami (神) produced in Japan at Matsuno’o Shrine (Jap. Matsuno’o taisha 松尾大社) in Kyoto (京都市) (and still housed there) is a key product from Enchin’s experiences with cosmopolitan continental East Asian Buddhist rituals. In the next section I investigate what Jōjin’s diary that covers the years 1072-1073, San Tendai Godaisan ki 參天臺五臺山記 [Record of a Pilgrimage to Mt. Tiantai and Mt. Wutai], tells us about his encounters with Central Asian and Indian teachers not only on Mt. Wutai (Chin. Wutai shan 五臺山) but also at the sūtra translation bureau known as the Institute for Transmitting the Dharma (Chin. Chuanfayuan 傳法院) on the grounds of the imperially sponsored monastery for Promoting Great Peace for the State (Chin. Taiping xingguo si 太平興國寺) in the Song capital of Bianliang (汴梁, modern Kaifeng 開封). Several of the rituals that Jōjin describes performing for Song Emperor Shenzong (1048-1085, 神宗) correspond to ceremonies we know were performed at the Daiun Temple (Jap. Daiun ji 大雲寺) and Jissōin (実相院) (located in the Iwakura (岩倉) section of northern Kyoto) and at key shrines like Matsuno’o, Kamigamo (上賀茂) and Shimogamo (下鴨) (in Kyoto), and Atsuta (熱田) (in Nagoya 名古屋) during the 12th-16th centuries. Finally, I describe how Buddhist—and Indic or Central Asian—rituals which were exchanged along the eastern Silk Road(s) during the 9th-11th centuries were employed in Japan with material culture (like statues and ritual paraphernalia) to venerate the kami by Tendai Jimon monastics using unambiguously cosmopolitan language to preserve the narrative of transmission along the Silk Road(s).